The importance of location factors in determining land prices: The evidence from Bratislava hinterland - Martin Mariés (REGION, 2021)
Bratislava, the capital city of Slovakia, is currently experiencing a period of intensive suburbanisation, which in turn creates demand pressures and increases the price of urban land located in its hinterland. This paper investigates several locational factors, which likely significantly influence the demand for land plots and modulate `price-maker' conditions. Based on the population sample of 102 units, the results indicate that built-in infrastructure facilities on land under analysis, advanced transport connectivity in municipalities, and various amenities in the municipality cadastre tend to elevate land prices significantly. Moreover, the factor of distance from the city of Bratislava plays a major role in household location, which was identified by the apparent decreasing rent gradient pattern.
Keywords: R11; R14; R31; 330; land economics; rent gradient; suburbanization; bid-rent function